KEANEKARAGAMAN IKAN DI SUNGAI KELINGI KOTA LUBUKLINGGAU - Dian Samitra; Zico Fakhrur Rozi (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2018)
This study aims to determine the diversity of freshwater fish in Kelingi River Lubuklinggau City. The research was conducted on 6 stations, the determination of the location of the research was done by purposive sampling method. Samples of fish obtained from the catch by using scatter and scoop-net and then identified in the Education Laboratory of Biology STKIP PGRI Lubukinggau. Data analysis includes species composition (KJ), diversity index (H ') and uniformity index (E). The results of identification there are 13 species belonged to 5 Order, 6 Family, and 13 genra. Barbonymus gonionotus has the largest type of composition (69.53%). Diversity index (H ' ) ranged from 0.33 to 1.22 and the uniformity index (E) ranged from 0.24 to 0.84. Conclusions the diversity index of Kelingi river in this study was low and fish communities at stations 1,3 and 6 under stable conditions and at station 2,4,5 under distress conditions